A FEW ASPECTS REGARDING THE SIMULATION OF CONTRACT IN THE ROMANIAN CIVIL CODE - Tudor Vlad RĂDULESCU (Challenges of the Knowledge Society)
The article aims to analyze some key aspects of simulation in contracts, as regulated by the Romanian Civil Code . The process of simulation will be explained, based on the provisions of the previous Civil Code, but also with reference to the relevant provisions of the legislation of some European countries. The analyse will focus on the apparent act, and also on the secret one and a special emphasis on intention to simulate, animo simulandi, the key aspect of the matter. Also the effects of the simulation will be reviewed, both from the point of view of the parties and that of third parties, the concept of third parties having another meaning in this procedure.